(Dielectric Science and Technology Division Thomas D. Callinan Award Address) Dielectrics for MOS Integrated Circuits. (18th April 2017) - Iwai, Hiroshi
Abstract : In this paper author's historical 45 year works for the development of the dielectrics for MOS Integrated Circuits are described as an invited talk as the recipient of 2017 ECS DS&T Thomas D. Callinan Award. Dielectric films has been the key components of the MOS LSI's since its beginning. The author's contributions include introduction of BPSG reflow technique into NMOS LSI technology, the finding of plasma induced damage to the gate oxide during ion implantation and reactive ion etching the introduction of RTN gate oxide to prevent the boron penetration, the introduction of direct-tunneling gate oxide for CMOS logic devices, and the demonstration of the 0.4 nm EOT Lasilicate gate oxide MOSFETs.